DIFFERENCES IN PSYCHOLOGICAL CHARACTERISTICS OF ELITE JUNIOR HANDBALL PLAYERS - Dóra KŐNIG-GÖRÖGH; Csaba ÖKRÖS; Noémi GYÖMBÉR (Cluj University Press, 2019)
The aim of the present paper is to investigate personality traits among junior handball players in different player positions and examine whether a standard can be established as to what personality traits the players in the individual positions should have. A Big Five Questionnaire survey was conducted in the early training period of 2016-2017 among elite Hungarian junior handball players (n=164, in terms of posts of playing players 25% were backcourt players, 23.2% wingers and 18.9% playmakers.). Big Five personality traits: Extroversion, Agreeableness, Conscientiousness, Neuroticism and Openness. Neuroticism showed significant differences by gender (t=3.9 p